2020
DOI: 10.1111/odi.13583
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐derived IgG involved in cisplatin resistance through PTP‐BAS/Src/PDK1/AKT signaling pathway

Abstract: Objectives This study aimed to explore whether knockdown of cancer‐derived IgG (CIgG) could enhance cisplatin‐induced anti‐cancer effects. Materials and methods Cancer‐derived IgG was knocked down by siRNA or Tet‐on shRNA in the absence or presence of cisplatin in WSU‐HN6 or CAL27 cells. Cell proliferation, apoptosis, and mobility were evaluated using CCK‐8, flow cytometry, and transwell assays, respectively. Molecular events were investigated using real‐time PCR and Western blot assays. Results Knockdown of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Generally, cancer-derived Ig is mainly detected in epithelial cancer cells, including those of breast cancer ( 12 15 ), colon cancer ( 16 , 17 ), cervical cancer ( 16 , 18 ), lung cancer ( 18 20 ), laryngeal cancer ( 21 ), nasopharyngeal cancer ( 22 ), pancreatic cancer ( 23 25 ), liver cancer ( 16 , 18 ), prostate cancer ( 26 28 ), oral cancer ( 29 , 30 ), thyroid cancer ( 31 ), parathyroid cancer ( 32 ), esophageal cancer ( 33 ), gastric cancer ( 34 ), renal cancer ( 35 ), and bladder cancer ( 36 ). At the subcellular level, cancer-derived Ig is mainly located in the cytoplasm and on the cell membrane.…”
Section: Wide Expression Of Ig In Cancer Cellsmentioning
confidence: 99%
“…Generally, cancer-derived Ig is mainly detected in epithelial cancer cells, including those of breast cancer ( 12 15 ), colon cancer ( 16 , 17 ), cervical cancer ( 16 , 18 ), lung cancer ( 18 20 ), laryngeal cancer ( 21 ), nasopharyngeal cancer ( 22 ), pancreatic cancer ( 23 25 ), liver cancer ( 16 , 18 ), prostate cancer ( 26 28 ), oral cancer ( 29 , 30 ), thyroid cancer ( 31 ), parathyroid cancer ( 32 ), esophageal cancer ( 33 ), gastric cancer ( 34 ), renal cancer ( 35 ), and bladder cancer ( 36 ). At the subcellular level, cancer-derived Ig is mainly located in the cytoplasm and on the cell membrane.…”
Section: Wide Expression Of Ig In Cancer Cellsmentioning
confidence: 99%
“…In recent years, increasingly more researchers have found that tumor cells can produce IgG, known as cancer-derived immunoglobulin G (CIgG) [7,[19][20][21]. Many studies have shown that CIgG plays an important role in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Although cancer-IgG was discovered in cancer cells decades ago, previous studies mainly focused on the relationship between cancer-IgG and tumorigenesis. Wang and Gan ( 28 ) found that knockdown of cancer-IgG can regulate the PTP-BAS/Src/PDK1/AKT pathway and thus significantly promote cisplatin-induced apoptosis and inhibition of oral squamous cell proliferation, migration, and invasion. Qin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although cancer-IgG was discovered in cancer cells decades ago, previous studies mainly focused on the relationship between cancer-IgG and tumorigenesis. Wang and Gan (28) found that knockdown of cancer-IgG can regulate the PTP-BAS/Src/PDK1/ AKT pathway and thus significantly promote cisplatin-induced apoptosis and inhibition of oral squamous cell proliferation, migration, and invasion. Qin et al (9) found that, in prostate cancer, cancer-IgG staining was stronger in specimens at advanced clinical stages; androgen deprivation therapy for prostate cancer-induced cancer-IgG expression maintained stemness and facilitated cancer progression through mitogenactivated protein kinase/extracellular signal-regulated kinase Building upon previous research, this study first explored the role of cancer-IgG in tumor radiotherapy and found that it is possible to mediate radiotherapy resistance by modulating the PI3K/AKT/DNA-PKcs signaling pathway.…”
Section: Discussionmentioning
confidence: 99%